Application of an inorganic sulfur-modified expanded graphite anode for sodium storage at low temperatures. Issue 20 (28th September 2021) - Zhou, Li-Feng; Gao, Yi-Jing; Gong, He; Liu, Li-Ying; Du, Tao
Abstract : An inorganic sulfur-modified expanded graphite was successfully prepared via both liquid fusion process and thermal expansion process. It exhibits high sodium storage and life-span performance at low temperature with the excellent kinetics. Abstract : Carbonaceous materials as anode materials are one of the candidates for commercial lithium ion batteries; meanwhile, they are potential for commercial sodium ion batteries. Graphite, as a member of them, plays an important role and needs to be further researched and modified. In this work, an inorganic sulfur-modified expanded graphite anode was prepared via both a liquid fusion process and a thermal expansion process, which presented a large interlayer distance of 3.77 Å. Furthermore, the capacity retention of more than 98% after 500 cycles at 0 °C was presented with a capacity of 245 mA h g −1 at 1C. In addition, in the most cold environment of high-latitude areas, when the temperature decreases to −20 °C, a capacity of 66 mA h g −1 means an actual availability. In addition, research of kinetics and cycled anodes showed a nice stability. Na + diffusion coefficients show nearly the same trend and values at room and low temperatures, and even after cycling still retain the same order of magnitude. Therefore, the inorganic sulfur-modified expanded graphite anode deserves to be considered a qualified anode material for the commercial application of sodium storage.